The description of a new calyptrate fly mimicking species of the fungus weevil genus Gymnognathus Schönherr 1826 from the southern Bolivian Andes (Coleoptera: Anthribidae: Anthribinae) - Perger, Robert; Guerra, Fernando (Zootaxa, 2016)
A new calyptrate fly mimicking species of Gymnognathus Schönherr 1826 from the humid Tucuman-Bolivian forest in the southern Bolivian Andes is described. Gymnognathus barclayi sp. nov. is distinguished from the closest related species G. bohlsi Jordan, 1895, by the color and/or distribution of the scales on the pronotum, fourth ventrite and pygidium, the wider pronotum and the development of the spines on the pygidium. The arrangement of the longitudinal stripes on the pronotum suggests that G. barclayi sp. nov. is a mimic of tachinid or muscid flies. The almost exclusive occurrence of Gymnognathus species in tropical moist forests indicates that the presence of G. barclayi sp. nov. in the subtropical realm is fostered by increased humidity at orographic rain barriers. G. barclayi sp. nov. is possibly endemic to the Tucuman-Bolivian forest. Along with the presence of other endemic species, the discovery of G. barclayi sp. nov. highlights the importance of the Tucuman-Bolivian forest as an endemism hotspot for insects and calls for a re-assessment of the conservation status of this spatially restricted and threatened ecoregion.